Mechanical Properties of Modification 5 Commercial Wood in NTB with Japanese Traditional Method – Yakisugi - Lestari, Andi Tri; Wahyuningsih, Endah; Suparyana, Pande Komang; Syaputra, Maiser; Fahrussiam, Fauzan (Jurnal Multidisiplin Madani, 2025)
Wood has hygroscopic properties so that the dimensional balance is unstable and favored by destructive organisms. In addition, wood exposed outdoors will easily undergo photodegradation by UV rays. One of the methods to improve the quality of wood is the Yakisugi method. This method is a traditional Japanese method that is environmentally friendly, more efficient, and economical. The application of the Yakisugi method can improve the quality of fast-growing wood that has low quality. This study was conducted to evaluate the mechanical properties of Yakisugi method on 5 commercial wood in NTB. The results of this research indicate the best charring time of yakisugi method is only 40 seconds charring, while the worst is 60 seconds charring and it is decrease the mechanical properties of all types of wood.